2021
DOI: 10.1007/s12325-021-01965-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lusutrombopag on Post-invasive Procedural Bleeding in Thrombocytopenic Patients with Chronic Liver Disease

Abstract: Introduction Thrombocytopenia can increase the bleeding risk in patients with chronic liver disease (CLD) undergoing invasive procedures. Prophylactic platelet transfusion (PT) is often performed to increase platelet counts in patients with CLD undergoing invasive procedures to prevent bleeding. Lusutrombopag, a small-molecule thrombopoietin receptor agonist, is expected to be an alternative therapy to prophylactic PT. This study aimed to compare the effects between lusutrombopag and PT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In addition, the efficacy and safety of the drug have been confirmed in a retrospective Japanese study based on hospital administrative databases. Here the incidence of bleeding events was lower in the lusutrombopag group than in the platelet transfusion group (3.7% vs 8.2%, P < 0.001), with a consequently lower average medical cost[ 85 ]. Finally, real-world data for adverse events (spontaneously reported by healthcare professionals and consumers in a database including about 4000 patients exposed to lusutrombopag from December 2015 to April 2018) confirm the efficacy and the safety of the drug (93% of patients did not require pre-procedural platelet transfusion; 1.2% of serious adverse events, with 0.4% cases of portal vein thrombosis)[ 86 ].…”
Section: New Therapeutic Options For Thrmbocytopenia In Chronic Liver...mentioning
confidence: 99%
“…In addition, the efficacy and safety of the drug have been confirmed in a retrospective Japanese study based on hospital administrative databases. Here the incidence of bleeding events was lower in the lusutrombopag group than in the platelet transfusion group (3.7% vs 8.2%, P < 0.001), with a consequently lower average medical cost[ 85 ]. Finally, real-world data for adverse events (spontaneously reported by healthcare professionals and consumers in a database including about 4000 patients exposed to lusutrombopag from December 2015 to April 2018) confirm the efficacy and the safety of the drug (93% of patients did not require pre-procedural platelet transfusion; 1.2% of serious adverse events, with 0.4% cases of portal vein thrombosis)[ 86 ].…”
Section: New Therapeutic Options For Thrmbocytopenia In Chronic Liver...mentioning
confidence: 99%
“…The proportion of patients who reported bleeding events was 2.23% (23/1033 patients), and lower than those of two previous studies: (1) a secondary analysis of lusutrombopag studies (phase 2b, L‐PLUS 1, and L‐PLUS 2) reporting a bleeding‐related AEs rate of 11.9% in patients receiving placebo with platelet transfusion and 6.5% in patients receiving lusutrombopag without platelet transfusion 21 ; and (2) a database study in Japan reporting bleeding events in 8.2% of the platelet transfusion group and 3.7% of the lusutrombopag treatment group 22 . These results suggested that lusutrombopag is an effective prophylactic treatment to prevent bleeding in CLD patients undergoing planned invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although hemorrhagic complications are rare with percutaneous ablation therapy, thrombocytopenia or platelet dysfunction in patients with chronic liver disease may increase the risk of post-operative bleeding following invasive procedures [28], and platelet transfusions may be advised in clinical practice for platelet counts <50,000/µL. Additionally, lusutrombopag, an orally active, small-molecule thrombopoietin receptor agonist that induces the production of endogenous platelets, may be used as prophylaxis to reduce the risk of bleeding [29,30]. However, the use of platelet transfusions to prevent post-operative bleeding is controversial because it has not yet been established whether prophylactic platelet transfusion is superior to no prophylaxis, if the platelet count threshold is appropriate as a guide to initiate the transfusion of prophylactic platelets, and what dose of platelets is needed to prevent post-operative bleeding [31,32].…”
Section: Low Platelet Count (Thrombocytopenia)mentioning
confidence: 99%